Intro to Java programmng Brief version - Liang, Y. Daniel (Pearson, 2015)
This text is intended for a 1-, 2-, or 3-semester CS1 course sequence. Daniel Liang teaches concepts of problem-solving and object-oriented programming using a fundamentals-first approach.